PENGARUH NIM, DEP, LOANS, dan SIZE TERHADAP CAR. (Studi Kasus Pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2012 – 2015) - Wuri Setyo Handayani, 13.05.51.0098 (Students' Journal of Economic and Management, 2017)
This study aims to analyze the influence of Net Interest Margin (NIM), Deposits (DEP), Loans (LOA), and Size Bank (SIZE) to Capital Adequacy Ratio (CAR) in banking listed in Indonesia Stock Exchange 2012- 2015. This study was conducted using secondary data. Population in this research is all banking listed in Indonesia Stock Exchange year 2012 – 1015. The sample in this research use purposive sampling method. The sample used in this research are 28 banking companies listed in Indonesia Stock Exchange (BEI) with purposive sampling technique, that is sample determination technique based on criteria. These criteria are banking companies listed on the BEI 2012- 2015 and submit complete financial and yearly reports. The hypothesis test showed that NIM has positive and significant effect to CAR, negative DEP is not significant to CAR, LOA is significant effect to CAR, and SIZE has negative and insignificant effect on CAR. Keywords: Net Interest Margin (NIM), Deposits (DEP), Loans (LOA), and Size Bank (SIZE) and Capital Adequacy Ratio (CAR).